2020
DOI: 10.1007/s00018-020-03454-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the protective effects of mesenchymal stem cell-based therapy

Abstract: Mesenchymal stem cells (MSCs) have been extensively investigated for the treatment of various diseases. The therapeutic potential of MSCs is attributed to complex cellular and molecular mechanisms of action including differentiation into multiple cell lineages and regulation of immune responses via immunomodulation. The plasticity of MSCs in immunomodulation allow these cells to exert different immune effects depending on different diseases. Understanding the biology of MSCs and their role in treatment is crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
314
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(328 citation statements)
references
References 292 publications
(300 reference statements)
5
314
1
8
Order By: Relevance
“…Recently, there has been interest in the regenerative properties of mesenchymal stromal cell (MSC) therapy for the repair and regeneration of damaged kidney tissue [11,12]. MSCs are a heterogeneous population of cells found in various adult tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been interest in the regenerative properties of mesenchymal stromal cell (MSC) therapy for the repair and regeneration of damaged kidney tissue [11,12]. MSCs are a heterogeneous population of cells found in various adult tissues.…”
Section: Introductionmentioning
confidence: 99%
“…There are various sources of MSCs, such as bone marrow, fat tissue, amniotic fluid, umbilical cord tissue, placental tissue, menstrual blood, salivary gland, Wharton jelly, dental pulp and pluripotent stem cells [ 10 , 11 ]. The therapeutic potential of MSCs is due to its differentiation into multiple cell lineages and regulation of immune responses via immunomodulation [ 12 ] MSCs can differentiate into epithelial, stromal, and endothelial cells, and have been shown to restore endometrial function and improve pregnancy outcomes [ 13 ]. Several studies have reported that MSC transplantation improves ovarian function and ovarian reserve, and this action may be mediated by paracrine signaling pathways [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem/stromal cells (MSCs) possess advantaged immunomodulatory and hematopoietic-supporting properties, together with a multi-lineage differentiation potential; they have been identified from numerous tissues and hold great promise for use in regenerative medicine (20)(21)(22)(23). Generally, the therapeutic effects of MSCs, include immunoregulation and tissue repair, mainly through direct-or trans-differentiation, in an autocrine and paracrine manner, as well as by supplying the microenvironment and homing methods (24)(25)(26)(27)(28). For decades, low-immunogenic MSCs have been shown to be safe and preferable for use in the management of recurrent and refractory diseases, such as spinal injury, type 2 diabetes, graft-vs.-host disease (GVHD), autoimmune diseases and hematological malignancies, as well as for severe influenza H5N1 caused by acute respiratory distress syndrome (ARDS) (20,24,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%